Disinfection of gloves: feasible, but pay attention to the disinfectant/glove combination. Issue 3 (November 2016) - Scheithauer, S.; Häfner, H.; Seef, R.; Seef, S.; Hilgers, R.D.; Lemmen, S.
Summary: Background: Compliance with hand hygiene is complicated by indications for hand disinfection in rapid succession during the care of one patient. In such situations, disinfection of gloves could facilitate better workflow and optimize compliance rates. Aim: We analysed the efficacy of disinfecting gloves by comparing an individual effect of five different hand disinfectant solutions in combination with three different glove types. Methods: The investigation was performed in accordance with DIN EN 1500:2013. For all combinations, ten analyses were performed, including (1) right/left-hand examination disinfection efficacy after the first and fifth contamination with E. coli K12 NCTC 10538, (2) recovery rates after contamination, (3) reduction efficacy, (4) fingertip immersion culture, and (5) check for tightness. Disinfection of the ungloved hands was taken as an additional benchmark. Findings: The disinfection efficacy for all disinfectant/glove combinations was better with rather than without gloves. For eight combinations, the disinfection efficacy was always >5.0 log10 . There were significant differences within the gloves ( P  = 0.0021) and within the disinfectant product ( P  = 0.0023), respectively. In detail, Nitril Blue Eco-Plus performed significantly better than Vasco Braun ( P  = 0.0017) and Latex Med Comfort ( P  = 0.0493). Descoderm showed a significantly worse performance than Promanum pure ( P  = 0.043). In the check for tightness, only the Vasco Braun gloves showed no leaks in all samples. There were relevant qualitative differences pertaining to the comfort of disinfecting gloves. Conclusion: The disinfection efficacy for the different disinfectant/glove combinations was greater than for the ungloved hands. However, various disinfectant/glove combinations produce relevant differences as regards disinfection efficacy.